(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
This scientific at work certification system methodical the basics international standards based on improvement issues analysis made. In particular, ISO, IEC, and international accreditation systems based on national certification methodologies of harmonization theoretical and practical aspects illuminated. Research as a result methodical instructions improvement model working issued and his/her efficiency based on given.